Synergistic catalytic mechanism and performance regulation strategies between nanoparticles/clusters and single-atom sites - Yifan Hu; Liangli Dai; Bolin Li; Changlin Yu; Zesheng Li (Materials Futures)
In recent years, nanoparticle/cluster catalysts and single-atom catalysts (SACs) have achieved remarkable advancements in catalytic applications, particularly in the energy and environmental sectors. SACs excel in catalysis through atomically dispersed active sites, while nanoparticle/cluster catalysts leverage their abundant surface properties and diverse active sites to enhance reaction rates and selectivity. To address the inherent limitations of individual catalysts in achieving high activity, selectivity and stability, researchers have developed hybrid catalysts that integrate these two systems, harnessing their synergistic effects. However, a comprehensive understanding of how to rationally construct and regulate these coexisting active sites remains limited. This article delves into the mechanisms underlying the coexistence of single-atom and nanocluster active sites, the structural diversity of hybrid catalysts and their dynamic transformation capabilities. By systematically analyzing the inter-site interactions, spatial configurations and synergistic behaviors, particular emphasis is placed on their synergistic effects during catalytic processes, including electronic structure modulation, bifunctional catalysis, relay catalysis and spatial confinement effects. Furthermore, hybrid catalysts demonstrate exceptional performance across practical applications, such as electrocatalysis, photocatalysis and thermal catalysis, offering new conceptual and design-based insights into developing green and efficient catalytic systems for future sustainable technologies.